Development and characterization of gelatin nanoparticles loaded with a cocoa-derived polyphenolic extract. (17th October 2014) - Quiroz-Reyes, Cinthya Nathaly; Ronquillo-de Jesús, Elba; Duran-Caballero, Nelson Eduardo; Aguilar-Méndez, Miguel Ángel
Abstract : Introduction . Polyphenols have received significant attention in recent years due to their antioxidant capacity and their significant role in disease prevention. Cocoa is one of the major naturally occurring sources of antioxidants, particularly of polyphenolic compounds.Materials and methods . Gelatin nanoparticles loaded with a cocoa-derived polyphenolic extract were synthesized by nanoprecipitation. The nanoparticle synthesis was performed using a central composite experimental design that allowed for the assessment of how gelatin concentration and surfactant concentration (Tween 80) affected the hydrodynamic diameter and polydispersity of the particles. The nanoparticles were characterized using dynamic light scattering (DLS), assessments of zeta potential, scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR).Results . The analyses demonstrated that the nanoparticles examined exhibited hydrodynamic diameters of (100 to 400) nm, polydispersity indices of less than 0.2 and average zeta potential values of 29–33 mV. SEM images revealed that most nanoparticles were spherical and uniform in morphology, with average sizes less than 250 nm. In vitro experiments in which the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) method was used to assess the prevalence of free radical-scavenging ability among these nanoparticles indicated that the loading efficiency for the nanoparticles was approximately 77.56%.Conclusion . Nanoparticles loaded with polyphenolic extract were obtained with average sizes ranging from (120 to 250) nm and largely spheroidal morphologies. Polymer and surfactant concentrations significantly influenced the hydrodynamic diameters and polydispersity indices of the particles. The incorporation of the polyphenolic extract into the polymer matrix enabled the preservation of the antiradical activity of the bioactive compound.